Сражение при Кунаксе: триумф эллинского оружия? - Беликов, А.П.; Нечитайлов, М.В. (My University, 2010)
Беліков А. П., Нечітайлов М. В. Битва при Кунаксі: тріумф еллінської зброї? Спираючись на свідоцтва широкого кола джерел та залучаючи велику історіографію, автори детально аналізують найбільш важливі питання битви при Кунаксі: співвідношення сил сторін та їх склад, хід бою, його підсумки та наслідки. На їхню думку, грецькі найманці фактично виграли бій, але реально його програв їх провідник Кір. В статті акцентується увага на значенні битви. Вона переконала еллінський світ в слабкості персидської держави, що мало далекосяжні наслідки як для еллінів, так і для персів. A. Belikov, M. Nechitaylov. The Battle under Ccunaxa: Triumph of the Hellenic Weapon? Resting in certificate of the broad circle of the sources and attracting extensive historiography, authors detailed analyze the most complex questions of the battle of Cunaxa: correlation of power of the sides and their composition, move of the battle, its totals and consequences. Upon their opinion, Greek mercenaries have practically won the battle, but real it had lost by their leader Cyrus. Attention is accented in article on importance of the battle. It has convinced the Hellenic world in weaknesses Persian state that had far going consequences both for Hellas, and for Persia.
Keywords: Cunaxa; Cyrus the Younger; Artaxerxes II; Xenophon; Ctesias